2015
DOI: 10.3390/s151229821
|View full text |Cite
|
Sign up to set email alerts
|

User-Independent Motion State Recognition Using Smartphone Sensors

Abstract: The recognition of locomotion activities (e.g., walking, running, still) is important for a wide range of applications like indoor positioning, navigation, location-based services, and health monitoring. Recently, there has been a growing interest in activity recognition using accelerometer data. However, when utilizing only acceleration-based features, it is difficult to differentiate varying vertical motion states from horizontal motion states especially when conducting user-independent classification. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…The proposed method was independent of the expert knowledge and greatly reduced the work of manual feature design, by the selection and combination of various sensors, the results showed that the classification performance by multiple sensors can be better than that by only accelerometers. Gu et al [29] developed a novel feature, called pressure derivative, which was obtained from the barometer embedded in the smartphone to recognize the motions in the vertical plane. In addition, they added the history information of the motion modes to the classification.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed method was independent of the expert knowledge and greatly reduced the work of manual feature design, by the selection and combination of various sensors, the results showed that the classification performance by multiple sensors can be better than that by only accelerometers. Gu et al [29] developed a novel feature, called pressure derivative, which was obtained from the barometer embedded in the smartphone to recognize the motions in the vertical plane. In addition, they added the history information of the motion modes to the classification.…”
Section: Related Workmentioning
confidence: 99%
“…The method can deal with the smartphone orientation and position well but hand and bag were not considered in their study. In [19], Gu et al explored the user-independent motion recognition using smartphone sensors. Different positions such as the trouser pocket, as well as holding with or without a swinging motion were studied during Information 2016, 7, 72 4 of 18 activity recognition.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to previous works [18][19][20][21][22], activity recognition can be divided into four steps: data collection, preprocessing, feature extraction and recognition. Firstly, raw data of smartphone sensors should be collected from users.…”
Section: The Design Of Pacp (Parameters Adjustment Corresponding To Smentioning
confidence: 99%
See 2 more Smart Citations